50 GHz active‐LC CMOS oscillator: Theoretical study and experimental proofs. Issue 9 (8th September 2017) - Pepe, Domenico; Chlis, Ilias; Zito, Domenico
Abstract: A 50 GHz cross‐coupled differential‐pair oscillator with a high‐Q active inductor in the LC tank has been designed and fabricated in 65 nm bulk complementary metal‐oxide semiconductor (CMOS) technology. The principle of operation is explained and a complete theoretical study is carried out. The analytical expressions for the open loop transfer function, oscillation frequency, start‐up condition, tank impedance, and phase noise are derived. The results of the analytical study are compared with those obtained by SpectreRF simulations in the Cadence design environment. Measurement results of the stand‐alone mm‐wave active inductor show an equivalent inductance of 133 pH with a quality factor exceeding 400 at 50 GHz, demonstrating experimentally the implementation of high‐Q active inductors operating at the millimeter waves in CMOS technology. The measurement results of the oscillator show a phase noise of −85 dBc/Hz at 1 MHz frequency offset from the carrier when the active inductor is switched off and −91 dBc/Hz when it is switched on, leading to a phased noise reduction of 6 dB. Key Points: This original manuscript expands and extends the contents reported in the short conference paper "50 GHz LC‐active oscillator in 65 nm CMOS" presented at the 2015 IEEE 15th Mediterranean Microwave Symposium (MMS), selected and invited for publication in Radio Science—Special Issue on "Innovative Microwave Devices, Methods, and Applications" A 50 GHz active‐LC oscillator in 65 nm CMOS has been designed and characterized experimentally A complete theoretical circuit analysis of the proposed oscillator has been carried out extensively in large details Plain Language Summary: A 50 GHz oscillator with a high‐Q active inductor in the LC tank has been designed and fabricated in 65 nm bulk CMOS technology. The principle of operation is explained and a complete theoretical study is carried out. The analytical expressions for the open loop transfer function, oscillation frequency, start‐up condition, tank impedance and phase noise are derived. The results of the analytical study are compared with those obtained by simulations. Measurement results of the stand‐alone mm‐wave active inductor show an equivalent inductance of 133 pH with a quality factor exceeding 400 at 50 GHz, demonstrating experimentally the implementation of high‐Q active inductors operating at the millimeter‐waves in CMOS technology. The measurement results of the oscillator show a phase noise of −85 dBc/Hz at 1 MHz frequency offset from the carrier when the active inductor is switched off and −91 dBc/Hz when it is switched on, leading to a phased noise improvement of 6 dB.